Pengembangan Media Jam Sudut pada Materi Pengukuran Sudut Siswa Sekolah Dasar - Ismail, Nur Afni C.; Pulukadang, Wiwy Triyanti; Marshanawiah, Andi (Jurnal Studi Guru dan Pembelajaran, 2024)
This research is research and development. The problem studied in this research is how to develop angle clock media in class IV angle measurement material at SDN 2 Kabila Bone? And what is the feasibility of developing angle clock medua in class IV angle measurement material at SDN 2 Kabila Bone? The purpose of this research is to determine the process of developing angle clock media in class IV angle measurement material at SDN 2 Kabila Bone. And identifying the feasibility of developing angle clock media in class IV angle measurement material at SDN 2 Kabila Bone. The subject of this research was class IV students at SDN 2 Kabila Bone, Bone Bolango Regency with a total of 21 people consisting of 9 boys and 12 girls. This research uses a research and development design that uses a development model, namely the ADDIE model. The data analysis techniques used in this research are qualitative and quantitative descriptive techniques. The results of this development research have reached the evaluation stage. Based on the results of validation by material experts, they obtained a score of 89.28%, from media experts they obtained a score of 91.66%, the results of the teacher response questionnaire obtained a percentage of 92.5%, the results of the student response questionnaire were 92.73% and for the evaluation results obtained the media obtained a percentage of 84.80%. Thus, the corner clock media developed is in the very suitable category for use in learning activities and can be continued at the next stage.